Etudes des bases génétiques et de la varibailité des caractères physiologiques impliqués dans la croissance chez l'huître creuse Crassostrea gigas - Collet, Bertrand; Boudry, Pierre; Bougrier, Serge; Heurtebise, Serge; Phelipot, Pascal; Ledu, Christophe; Morand, Berenice; Heral, Maurice; Gerard, Andre (Actes Journées Conchylicoles, Ifremer Nantes, 18-19 mars 1997, 1997)
A European programme (GENEPHYS) was launched in 1996 to study the genetic basis and variability of physiological characters involved in growth in Crassostrea gigas. This research programme was a prerequisite for any genetic selection programme on physiological functions. Research groups from Ireland, England, Greece and France are involved in this project and participate in genetic analyses (allozymes and microsatellites) and physiological analyses (ecophysiology, enzymology, stress proteins). Ifremer at La Tremblade was responsible for producing the biological material while Ifremer-CREMA (human-influenced marine ecosystems research centre) was responsible for carrying out non-destructive physiological analyses. Un programme européen ("GENEPHYS") a été initié en 1996 dans le but d'étudier les bases génétiques et la variabilité des caractères physiologiques impliqués dans la croissance de Crassostrea gigas, étape nécessaire à toute sélection génétique sur le rendement métabolique. Des équipes irlandaises, anglaises, grecques et françaises sont impliquées dans ce projet et participent aux analyses génétiques (allozymes et microsatellites) et physiologiques (écophysiologie, enzymologie, protéines de stress). La production de matériel biologique est assurée par l'IFREMER de La Tremblade tandis que les analyses physiologiques non destructives sont assurées par le CREMA.